(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
Currently, the main pedagogical technologies are imperial, cognitive, heuristic, creative, inversion, adaptive, inclusive and other technologies. Knowing how to choose these technologies during the lesson depends on the teacher’s skills. Pedagogical technology in education is to engage students in education and to achieve full mastery of knowledge, to create an opportunity for students to express their opinions. The most important requirement in teaching in the process of pedagogical technology is providing knowledge based on the student’s life experience, previously acquired knowledge and interests.